'Better' cycle engines. (4th August 2014) - Pavletic, R.; Prebil, I.; Vuksanovic, B.
In conventional internal combustion engines the indicated cycles are well presented by ideal Otto, Diesel or Sabathee cycles. Regarding the working capability, here cycles do not reach the Ericsson cycle, having, inside the given temperature and pressure boundaries, the highest working capability, and exploiting the heat regeneration that is the efficiency of the Carnot cycle. In this article some useful models of 'better' indicated cycles are introduced and explored in working conditions similar to modern engines. The mechanical equipment making the cycle run possible is proposed and analysed, regarding the limits originating in the particularities of its mechanisms, properties of its materials and the medium used. Ideas of construction solutions of such engines are presented, supported by fundamental calculations of the processes.